Unveiling the Decision-Making Process of Digital Transformation Adoption from a Behavioral-Cognitive Perspective: Mediating and Moderating Mechanisms - Pham, Thong Van; Tran, Thuc Duc (Emerging Science Journal, 2025)
Although digital transformation (DT) is an unavoidable trend today, achieving successful DT presents numerous challenges. Problem-solving skills (PSS) and knowledge barriers in the digital age are among the most pressing issues. Given this premise, this research aims to unveil the “decision-making related to digital transformation adoption (DTDM)” via the cognitive processes and PSS. The study conducted an online survey with 516 current employees of Vietnamese enterprises to evaluate the measurement and structural models and to clarify the nexuses between low cognitive level (LCL), high cognitive level (HCL), PSS, and DTDM. The research results show that LCL, HCL, and PSS are positively associated with DTDM, with HCL and PSS mediating the relationship between LCL and DTDM. In addition, the study also pointed out the moderating role of creativity (CRT) in the association between LCL and DTDM. Consequently, the study makes significant practical and theoretical contributions to DT and helps address current bottlenecks related to the barriers to DT. Doi: 10.28991/ESJ-2025-09-01-023 Full Text: PDF